INTRODUCTION, CONNECTION, APPLICATION, REFLECTION AND EXTEND (ICARE) MODEL IN TEACHING SPEAKING - Nunung Anugrawati (UIN Alauddin Makassar, 2016)
Abstract This study was intended to improve the students’ ability in speaking through ICARE model at the third semester students of English Department of Muhammadiyah University of Makassar. This research employed Classroom Action Research consisting of two cycles where each cycle consisted of four meetings. The instrument used in this research was speaking test. The data obtained from the test in the end of each cycle was analyzed quantitatively. The findings showed that there was significant improvement on the students’ speaking ability in terms of accuracy and fluency in which the mean score of diagnostic test was 5.17, the mean score of cycle I was 6.06 and the mean score of cycle II was 7.21. AbstrakPenelitian ini dimaksudkan untuk meningkatkan kemampuan siswa dalam berbicara melalui model ICARE mahasiswa semester III Departemen bahasa Inggris di Universitas Muhammadiyah Makassar. Penelitian ini menggunakan penelitian tindakan kelas yang terdiri dari dua siklus yang mana setiap siklus terdiri dari empat pertemuan. Instrumen yang digunakan dalam penelitian ini adalah Tes speaking. Data yang Diperoleh dari tes di akhir setiap siklus dianalisis secara kuantitatif. Temuan menunjukkan bahwa ada peningkatan yang signifikan pada kemampuan berbahasa siswa dalam hal ketepatan dan kelancaran di mana nilai rata-rata tes diagnostik adalah 5.17, Skor rata-rata pada siklus I adalah 6.06 dan skor rata rata pada siklus II adalah 7.21.